Advances in Wood Composites (2020)
Wood composites have shown very good performance, and substantial service lives when correctly specified for the exposure risks present. Selection of an appropriate product for the job should be accompanied by decisions about the appropriate protection, whether this is by design, by preservative treatment or by wood modification techniques. This Special Issue, Advances in Wood Composites presents recent progress in enhancing and refining the performance and properties of wood composites by chemical and thermal modification and the application of smart nanomaterials, which have made them a particular area of interest for researchers. In addition, it reviews some important aspects in the field of wood composites, with particular focus on their materials, applications, and engineering and scientific advances, including solutions inspired biomimetrically by the structure of wood and wood composites. This Special Issue, with a collection of 13 original contributions, provides selected examples of recent Advances in Wood Composites